THE INFLUENCE OF BRAND AMBASSADOR CREDIBILITY, SOCIAL MEDIA ADVERTISING PERCEIVED INFORMATIVENESS AND SOCIAL MEDIA ADVERTISING PERCEIVED ENTERTAINMENT ON INSTAGRAM @BLIBLIDOTCOM TOWARDS INTENTION TO USE BLIBLI AS ONLINE SHOPPING PLATFORM - Zelda Elsa Khabibah; Tandiyo Pradekso; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Blibli as an Indonesian e-commerce company intensely implemented marketing strategies, but number of monthly website visitors has decreased, and the company is not yet a market leader. This study aims to determine the influence of brand ambassador credibility, social media advertising perceived informativeness and social media advertising perceived entertainment towards intention to use Blibli. This study uses the Source Credibility model and Expectancy Value theory to explain the hypotheses. This study used a non-probability sampling technique with total of 256 respondents with the characteristics of men or women in Indonesia, aged 18-33 years old, who know Blibli's brand ambassador and have seen Blibli's social media advertising on Instagram @bliblidotcom. Data analysis was carried out using simple linear regression and multiple linear regression processed in SPSS version 25. The first hypothesis test shows that there is a positive influence of brand ambassador credibility on intention to use, as evidenced by a significance value of 0.000 (<0.01). Furthermore, the second hypothesis test also shows that there is a positive influence of social media advertising perceived informativeness and social media advertising perceived entertainment on the intention to use Blibli as an online shopping platform, as evidenced by a significance value of 0.000 (<0.01).